A new Bursaphelenchus species (Nematoda: Parasitaphelenchidae) sharing characters with Ektaphelenchidae from the People s Republic of China - Braasch, Helen (Zootaxa, 2004)
Several pine wood and bark samples from the suburban forest of Nanjing, China were investigated for the occurrence of Bursaphelenchus species. Both samples collected from damaged or dead Pinus thunbergii and Pinus massoniana, which were also attacked by B. xylophilus, revealed the presence of Bursaphelenchus lini sp. n. The new species is 673 (450 800)/ 898 (696 1100) m long for males and females, resp., has a 19 (17 21)/ 20 (18 23) m long stylet lacking basal knobs or swellings, three lateral lines, 16 21 m long spicules with a high condylus and a finely rounded rostrum almost in the middle of the spicules, a distinct bursa at the male tail terminus, and a tapering female tail with a curved, slightly ventrally bent terminus and finely rounded end. The vagina is wide with strong half ring-like sclerotization in its anterior part. The relatively short postuterine branch is about 1.5 body diam. long. Bursaphelenchus lini sp. n. is similar to B. teratospicularis, B. hylobianum, B. abietinus, B. hellenicus and B. rainulfi in the shape of spicules and female tail. It differs from the last four species by the longer stylet and spicules as well as by vulval shape and from B. teratospicularis by the somewhat different shape of the female tail (terminus thinner and more ventrally bent in B. lini sp. n.), the lack of basal thickenings of the stylet, the greater body length (673/ 898 m vs 606/673 m), and the different shape of the distal end of spicules. Bursaphelenchus lini sp. n. shares characters of Bursaphelenchinae (Parasitaphelenchidae), i. e. vulva position at 76%, strongly recurved male tail and distinct terminal bursa, and some characters of Ektaphelenchidae, i. e. inconspicuous rectum and anus, intestine ending in a blind sac, posterior position of the valve plates in the median bulb, strongly sclerotized vagina and relatively broad lumened stylet.